Strategi Marketing Public Relations Kopi Kenangan dalam Membangun Brand Awareness - Scelly Alvionita Chayadi; Riris Loisa; Sudarto Sudarto (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
The rapid growth of the coffee business in Indonesia especially JABODETABEK, has resulted in very tight competition for entrepreneurs in the coffee sector, this has made coffee shop entrepreneurs have to be able and must have the right strategy in dealing with this competition. The purpose of this study is to determine the Marketing Public Relations strategy of Kopi Kenangan in building brand awareness for the last 3 years. The theory used in this research is Whalen's 7 step Strategic Planning Process. The method used in this research is qualitative with the case study method. The data collection technique used was in-depth interviews. The results of this study indicate that the Marketing Public Relations of Kopi Kenangan wants to instill the mindset of